Clinical phenotypes in adult patients with bronchiectasis. Issue 4 (4th February 2016) - Aliberti, Stefano; Lonni, Sara; Dore, Simone; McDonnell, Melissa J.; Goeminne, Pieter C.; Dimakou, Katerina; Fardon, Thomas C.; Rutherford, Robert; Pesci, Alberto; Restrepo, Marcos I.; Sotgiu, Giovanni; Chalmers, James D.
Bronchiectasis is a heterogeneous disease. This study aimed at identifying discrete groups of patients with different clinical and biological characteristics and long-term outcomes. This was a secondary analysis of five European databases of prospectively enrolled adult outpatients with bronchiectasis. Principal component and cluster analyses were performed using demographics, comorbidities, and clinical, radiological, functional and microbiological variables collected during the stable state. Exacerbations, hospitalisations and mortality during a 3-year follow-up were recorded. Clusters were externally validated in an independent cohort of patients with bronchiectasis, also investigating inflammatory markers in sputum. Among 1145 patients (median age 66 years; 40% male), four clusters were identified driven by the presence of chronic infection with Pseudomonas aeruginosa or other pathogens and daily sputum: " Pseudomonas " (16%), "Other chronic infection" (24%), "Daily sputum" (33%) and "Dry bronchiectasis" (27%). Patients in the four clusters showed significant differences in terms of quality of life, exacerbations, hospitalisations and mortality during follow-up. In the validation cohort, free neutrophil elastase activity, myeloperoxidase activity and interleukin-1β levels in sputum were significantly different among the clusters. Identification of four clinical phenotypes in bronchiectasis could favour focused treatments in future interventional studies designed to alter the natural history of the disease. Daily sputum and chronic infection with Pseudomonas or other bacteria define clinical phenotypes in bronchiectasis http://ow.ly/W4H9m